Optimal parameters of viscoelastic tuned-mass dampers. (14th April 2019) - Batou, A.; Adhikari, S.
Abstract: A vibration absorber, also known as a tuned mass damper (TMD), is a passive vibration control device. This is achieved by attaching a secondary oscillator to a primary oscillator. In general, the aim is to reduce the vibration of the primary oscillator by suitably choosing the parameters of the secondary oscillator. The effectiveness of a TMD depends on (a) optimised the value of the tuned parameters, and (b) the nature of ambient damping of the absorber. They theory of TMD when the secondary and the primary oscillators are undamped or viscously damped is well developed. This paper presents an analytical approach to obtain optimal parameters of a TMD when the vibration absorber is viscoelastically damped. Classical results on viscously damped vibration absorbers can be obtained as a special case of the general results reduced in the paper. It is shown that by using a viscoelastically damped TMD, it is possible to obtain superior vibration absorption compared to an equivalent viscously damped TMD.